FENOMENA KOMUNIKASI WANITA KARIR SINGLE PARENT DIKOTA PEKANBARU - Vidya Astri Wahyuni; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Career women who are single parent is no longer ordinary to be performed thanks to women emancipation that make women are equal to men and no longer considered as taboo in the public opinion. Without their spouse, a single parent woman can be a success in raising kids and their career. Woman prefer to retain divorced from marriage, while living uncomfortable. A woman will prefer to ask for divorce rather than struggle with irritating marriage. A woman who wants to be a housewife but they have to face financial problems in their life and at the end, they have to work outside with all their efforts. This study aims to reveal motive in the future that by holding single parent status, its meaning, and reveal communication experiences for career women who is single parent in Pekanbaru City.This study uses qualitative research method with phenomenology approach. Subject for this study are 3 (three) career women who is single parent in Pekanbaru City which categorized by purposif method and obtained by using snowball technique. Data collection obtained by deep interview, observation, and literature study.Study result concludes that motives for career women in the future with single parent status are struggle, life style, and craving for activities. Whilst other motives are to achieve success and hoping for new spouse. Meaning that they have to keep is accepting their status as single parent and convince to live independently. Communication experience categorized into 2 groups, which are positive communication experience, such as advice from family, support from relatives to live, good suggestion from environment, and negative communication experience such as gossip for their single parent status, family talk, and widow status which always being debate topic in their neighborhood and colleagues.Keyword: phenomenon, career women, single parent, motives, meaning, communication experience